MORPHOLOGY OF THE LIVER AND KIDNEYS IN HEPATIC-RENAL SYNDROME IN DOGS AND CATS - Локес, П. І.; Кравченко, С. О.; Грищук, А. В.; Локес-Крупка, Т. П. (Scientific Progress & Innovations, 2014)
Studies have found that the development of hepatocellular renal syndrome in dogs and cats is accompanied by structural changes in the liver and kidneys. Pathological changes were to increase, edema and focal discolored liver and kidneys. Microscopic changes consist in the development of protein (granular and hydropic) degeneration, focal necrosis of hepatocytes and manifestations extracapillary glomerulonephritis and interstitial nephritis, atrophy most convoluted tubules and glomeruli.